2017
DOI: 10.1007/s12020-017-1266-9
|View full text |Cite
|
Sign up to set email alerts
|

Presence of headache and headache types in patients with tumors of the sellar region—can surgery solve the problem? Results of a prospective single center study

Abstract: Apart from pituitary apoplexy we detected no specific headache type in our patient group and no significant improvement of headache after neurosurgery. Headache alone constitutes neither a valid diagnostic marker for the presence of tumors of the sellar region nor a sufficient indication for tumor removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 32 publications
10
35
1
1
Order By: Relevance
“…Bearing in mind the absence of any mass effect on the cavernous sinus or optic chiasm, tumor size seems to play no prominent role in the pathogenesis of PA‐related headache in our case. In a recent study, headaches in patients with pituitary tumors were suggested to occur more often in absence of cavernous sinus invasion and optic chiasm compression . Inflammation related to the necrosis leading to local trigeminal nociceptor excitation might be suggested in our specific case of TAC.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Bearing in mind the absence of any mass effect on the cavernous sinus or optic chiasm, tumor size seems to play no prominent role in the pathogenesis of PA‐related headache in our case. In a recent study, headaches in patients with pituitary tumors were suggested to occur more often in absence of cavernous sinus invasion and optic chiasm compression . Inflammation related to the necrosis leading to local trigeminal nociceptor excitation might be suggested in our specific case of TAC.…”
Section: Discussionmentioning
confidence: 75%
“…In a recent study, headaches in patients with pituitary tumors were suggested to occur more often in absence of cavernous sinus invasion and optic chiasm compression. 2 Inflammation related to the necrosis leading to local trigeminal nociceptor excitation might be suggested in our specific case of TAC. Moreover, in patients with pituitary adenomas, functioning rather than nonfunctioning adenomas were more likely to be associated with TACs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Außerdem verschwindet der Kopfschmerz nicht notwendigerweise nach der Tumorentfernung, so z. B. bei Tumoren der Sella-Region (23). Die eigentliche Hirntumortherapie ist auch nicht Gegenstand dieser Übersicht.…”
Section: Therapeutische Prinzipienunclassified